Assessment of Pathological Complete Response Using Vacuum-Assisted Biopsy in Breast Cancer Patients Who Have Clinical and Radiological Complete Response After Neo-Adjuvant Chemotherapy - Siddhant Khare; Irrinki Santosh; Ishita Laroiya; Tulika Singh; Amanjit Bal; Gurpreet Singh (Breast Cancer: Basic and Clinical Research, 2023)
Background: Any treatment protocol that leads to complete elimination of surgery may lead to a better patient acceptance of breast cancer treatments. Objectives: We conducted this study to assess the feasibility of preoperative vacuum-assisted biopsies in identifying pathological complete response (pCR) and its accuracy in correlation to final histopathology report (HPR), in an Indian setting. Methods: This was a prospective study conducted between October 1, 2019, and March 31, 2021. Patients with early breast cancer, estrogen and progesterone receptors negative and either Her2 positive or negative, and who were fit to undergo marker placement at the centre of the tumour and to receive third-generation chemotherapy (4 cycles of 3 weekly doxorubicin and cyclophosphamide followed by 4 cycles of 3 weekly docetaxel) were included in the study. Following the enrolment, a tissue marker was placed at the centre of the tumour and appropriate chemotherapy was started. Patients who achieved clinical complete response were subjected to ultrasound-guided vacuum-assisted biopsy (VAB) from the tumour bed before surgery. Pathology results of the VAB and resected specimen were then compared. Descriptive statistics were used in the study. Results: Eighteen patients were enrolled in the study, with a mean age of 43.6 ± 9.8 years. However, only 10 were eligible for VAB procedure, and sensitivity and specificity were calculated based on the results of these 10 patients only. Vacuum-assisted biopsy showed sensitivity of 50% and specificity of 100% in identifying pCR. Combination of mammography, ultrasonography, and VAB showed sensitivity of 77.8% and specificity of 66.7% in identifying pCR. Conclusion: Vacuum-assisted biopsy of tumour bed may not be sensitive enough to eliminate surgery even in patients who have had exceptional response to neo-adjuvant chemotherapy.